Investasi Bodong Berkedok Kerja Sama: Wanprestasi dalam Perjanjian Penanaman Modal Usaha Kecil - Aisyah Asiyah; Dian Octavia; Suci Nurhamidah (Hukum Inovatif : Jurnal Ilmu Hukum Sosial dan Humaniora, 2026)
This study examines fraudulent investment practices disguised as small-scale business investment cooperation agreements, focusing on aspects of breach of contract (wanprestasi), the validity of agreements, investor losses, as well as legal protection and dispute resolution mechanisms. This research employs a normative juridical method with a descriptive-analytical approach through library research on various laws and regulations, legal doctrines, and relevant literature. The findings show that fraudulent investment practices are generally packaged in cooperation agreements that appear formally valid and meet administrative requirements; however, substantively they are not based on good faith and often contain elements of misleading information. This condition results in breaches of contract that cause both material and immaterial losses to investors and has the potential to lead to legal disputes between the parties. Legal protection for investors can be provided through preventive mechanisms such as regulation and supervision, as well as repressive mechanisms through law enforcement. Meanwhile, dispute resolution can be carried out through negotiation, mediation, arbitration, or civil litigation in court in accordance with applicable legal provisions. Therefore, caution is required in the drafting and implementation of investment agreements to avoid harming any party and to ensure legal certainty and the creation of a healthy, safe, and fair investment climate for all parties involved, including strengthening public legal literacy on an ongoing basis and being oriented toward investor protection.